1987
DOI: 10.1073/pnas.84.15.5459
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial and fibroblast growth factors have neurotrophic functions for cultured peripheral and central nervous system neurons.

Abstract: Embryonic and neonatal neurons require specific trophic supplements for their survival and the induction of transmitter-synthesizing enzymes in vivo and in vitro. Acidic and basic fibroblast growth factor (aFGF, bFGF) and the closely related astroglial growth factors AGF-1 and AGF-2 were studied for putative neurotrophic functions using dissociated, highly neuron-enriched cultures from chick and rat peripheral ganglia and central nervous system tissues. Embryonic chick ciliary ganglion neurons were the only pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
191
3

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(198 citation statements)
references
References 33 publications
4
191
3
Order By: Relevance
“…la ) revea ls a Cterminally ex tended product. CNTF, rather, see ms 10 be a molecule simil ar to FGF o r interleukin-l (lL-l ) both of wh ich exert profound effects on cells but are cytoplasmic proteins. For FGF, no release mechani sm has been estab lished 12 , By contrast, IL-l has been demonstrated 10 be released from stimul ated Amino-acid composition of CNTF.…”
Section: Larmentioning
confidence: 99%
“…la ) revea ls a Cterminally ex tended product. CNTF, rather, see ms 10 be a molecule simil ar to FGF o r interleukin-l (lL-l ) both of wh ich exert profound effects on cells but are cytoplasmic proteins. For FGF, no release mechani sm has been estab lished 12 , By contrast, IL-l has been demonstrated 10 be released from stimul ated Amino-acid composition of CNTF.…”
Section: Larmentioning
confidence: 99%
“…Neurotrophic activity of bFGF-enriched fractions was tested in a bioassay using chick ciliary ganglionic neurons of embryonic day 8 (cCG 8) [6]. To establish plateau survival values we used saturating concentrations of purified or recombinant bovine bFGF [6] (recombinant bFGF was kindly provided by PROGEN, Heidelberg) or CNTFcontaining cell-free extracts from selected embryonic chick eye tissues (CIPE) (221.…”
Section: Bioassaymentioning
confidence: 99%
“…To establish plateau survival values we used saturating concentrations of purified or recombinant bovine bFGF [6] (recombinant bFGF was kindly provided by PROGEN, Heidelberg) or CNTFcontaining cell-free extracts from selected embryonic chick eye tissues (CIPE) (221. Culture medium without trophic factors served as the baseline control.…”
Section: Bioassaymentioning
confidence: 99%
“…The peptide has been demonstrated to have a role in stimulating hippocampal neurogenesis (Palmer et al, 1999) and, and in some model systems, has been reported to have neurotrophic actions. For example FGF-2 promotes survival of cultured cerebellar granule cells (Bonthius et al, 2003) as well cultured embryonic chick ciliary ganglion neurons and cultured spinal chord neurons (Unsicker et al, 1987). It has been additionally reported to enhance survival of hippocampal neurons in culture (Walicke et al, 1986), and to confer protection from glutamate-induced cell death (Mattson et al, 1995;Lenhard et al, 2002).…”
Section: Introductionmentioning
confidence: 99%